Surgical excision margins in primary cutaneous melanoma: A systematic review and meta-analysis. Issue 7 (July 2021) - Hanna, Sarah; Lo, Serigne N.; Saw, Robyn PM.
Abstract: Background: The main treatment of primary cutaneous melanoma is surgery. This review aims to assess the width of excision margin that minimises the risk of adverse outcome from surgery, locoregional recurrence, distant recurrence, and death. Methods: PRISMA guidelines were followed. MEDLINE, EMBASE, and four other databases were searched by using the term "melanoma", "margin", and limiting the search to randomised clinical trials (RCTs). Results: Seven RCTs involving 4579 patients data were analysed. No statistically significant difference was found in locoregional recurrence RR 1.09 (95%CI 0.98–1.22, p = 0.12), local recurrence RR 1.20 (95%CI 0.66–2.21, p = 0.55), in-transit metastasis RR1.30 (95%CI 0.86–1.97, p = 0.21), regional nodal metastasis RR 1.04 (95%CI 0.91–1.18, p = 0.56), distant metastasis RR 0.95 (95%CI 0.72–1.24, p = 0.68), death RR 1.00 (95%CI 0.93–1.07, p = 0.97), death from melanoma RR 1.11 (95%CI 0.96–1.28, p = 0.16), wound infection RR 1.22 (95%CI 0.68–2.17, p = 0.50), and wound dehiscence RR 0.96 (95%CI 0.54–1.71, p = 0.88) when narrow (1–2 cm) versus wide (3–5 cm) excision margins were compared. In contrast, patients with narrow excision margins had a significant reduction in complex surgical reconstruction RR 0.30 (95%CI 0.19–0.49, p < 00001). When studies were excluded because of high risk of bias the only significant difference was death due to melanoma RR 1.25 (95%CI1.01–1.55, P = 0.04). Conclusions: No significant difference between narrow and wide excision margins in locoregional or distant recurrence, metastasis, death, or death due to melanoma. Wide margins (2–5 cm) increased the need for surgical reconstruction. Further studies are needed to assess optimal excision margins with regards to Breslow thickness and other prognostic factors and are in progress.